Personality traits and meat consumption: The mediating role of animal-related ethical concerns - Haefner, Gonzalo; Schobin, Janosch; Risius, Antje (Frontiers in Psychology, 2023)
Prior research suggests that personality traits are associated with meat consumption. However, this association is not uniform across all types of meat. For instance, Big Five personality traits such as openness and agreeableness are negatively associated with red meat consumption but positively associated with fish. Using a large sample of Chilean university students (N = 1,149), we examined whether these differential meat consumption patterns can be explained by an intermediary variable of animal-related ethical values. Structural equation modelling was employed to test the hypothesized associations. The results suggest that animal-related ethical values mediate the effect of certain personality traits on the consumption of beef and poultry.